Penggunaan Poly Gel dalam Peningkatan Estetika Nail Art pada Teknik 3D - Syahrani Gusvita; Siska Miga Dewi (YASIN, 2026)
Although 3D nail art is increasingly developing in the field of makeup and beauty, variations in poly gel application techniques for 3D nail art designs remain limited, which may affect customers’ interest in the designs offered. This study aims to describe the results of applying poly gel with flora motifs to 3D nail art designs in terms of beauty, neatness, texture, and preference. This study used a quantitative descriptive method with an experimental design. The object of the study was the use of poly gel in 3D technique nail art designs applied to false nails (fake nails) with flora motifs. The research procedure included the stages of preparation, experiment implementation, observation and assessment, data collection, data analysis, conclusion drawing, and recommendation formulation. The assessment was conducted by nine panelists consisting of two individuals from the hand care field, two individuals from nail art specialty salons, and five makeup and beauty students from the 2021 cohort who frequently use nail art. Data were collected through observation and documentation, and were then analyzed using a percentage formula. The results showed that the use of poly gel in 3D technique nail art received positive assessments in terms of beauty, neatness, texture, and preference. In terms of beauty, the designs were predominantly rated in the beautiful and very beautiful categories. In terms of neatness, most panelists rated the nail art results as neat to very neat. In terms of texture, the 3D nail art designs made with poly gel were assessed as having a smooth surface and being visually comfortable. In terms of preference, the panelists generally liked the 3D nail art designs using poly gel. The conclusion of this study affirms that poly gel with flora motifs can be used as an alternative material and technique in developing 3D nail art designs that are aesthetic, neat, smooth-textured, and favored by users.